1999
DOI: 10.2105/ajph.89.4.553
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of environmental hazards in the homes of older persons.

Abstract: OBJECTIVES: This study sought to estimate the population-based prevalence of environmental hazards in the homes of older persons and to determine whether the prevalence of these hazards differs by housing type or by level of disability in terms of activities of daily living (ADLs). METHODS: An environmental assessment was completed in the homes of 1000 persons 72 years and older. Weighted prevalence rates were calculated for each of the potential hazards and subsequently compared among subgroups of participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 24 publications
5
49
1
5
Order By: Relevance
“…As noted in other studies, 7,10,11 environmental hazards were present in nearly all dwelling units. The home safety assessments by occupational therapists revealed an average of 10 hazards per dwelling unit, the most common being absence of suitably placed grab rails in the bathroom and/or toilet (see Figure 1).…”
Section: Discussionsupporting
confidence: 77%
“…As noted in other studies, 7,10,11 environmental hazards were present in nearly all dwelling units. The home safety assessments by occupational therapists revealed an average of 10 hazards per dwelling unit, the most common being absence of suitably placed grab rails in the bathroom and/or toilet (see Figure 1).…”
Section: Discussionsupporting
confidence: 77%
“…The increased postural instability under dim lighting conditions might contribute to this increased risk of falling -and, of course, under such conditions, there is an increased likelihood that potential obstacles will not be detected. Nearly half of a sample of US community-dwelling older people had dim lighting in at least one room [13], whilst 1 of 5 older people in a UK study reported not using the light at all when moving around the house at night [14]. Encouraging older people to install and use adequate lighting (at least 10 lx) might thus reduce the risk of falls in the home.…”
Section: Discussionmentioning
confidence: 99%
“…1999 yılında yaptıkları toplum temelli çalışmada, toplumda yaşayan yaşlı kişilerin evlerindeki çevresel tehlikelerin yaygın olduğunu bulmuşlardır (24). Yine bu çalışmada banyo en tehlikeli alan olarak bulunmuştur.…”
Section: Discussionunclassified